2013
DOI: 10.1007/s00392-013-0618-6
|View full text |Cite
|
Sign up to set email alerts
|

The biophysics of renal sympathetic denervation using radiofrequency energy

Abstract: Renal sympathetic denervation is currently performed in the treatment of resistant hypertension by interventionists who otherwise do not typically use radiofrequency (RF) energy ablation in their clinical practice. Adequate RF lesion formation is dependent upon good electrode-tissue contact, power delivery, electrode-tissue interface temperature, target-tissue impedance and the size of the catheter's active electrode. There is significant interplay between these variables and hence an appreciation of the bioph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 27 publications
0
27
0
1
Order By: Relevance
“…RSD is an interventional treatment option in resistant HT when optimal medical treatment fails [7][8][9][10][11][12][13][14][15][16][17]. However, data from the randomized, blinded HTN-3 trial did not show a significant reduction of SBP in patients with resistant HT compared with sham controls 6 months after RSD [18].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…RSD is an interventional treatment option in resistant HT when optimal medical treatment fails [7][8][9][10][11][12][13][14][15][16][17]. However, data from the randomized, blinded HTN-3 trial did not show a significant reduction of SBP in patients with resistant HT compared with sham controls 6 months after RSD [18].…”
Section: Discussionmentioning
confidence: 97%
“…The RSD systems currently in use, with single or multiple electrodes, do not provide intra-procedural feedback on successful denervation of the sympathetic nerve fibers that are the target of this specific interventional therapy. Up until now, there is limited clinical evidence confirming a successful reduction of the sympathetic activity after RSD [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…27,28 The effectiveness of the radiofrequency procedure with adequate lesion formation is dependent on electrode-tissue contact, power delivery, electrode-tissue interface, temperature, and target tissue impedance, which all affect the depths of the lesions. 27 For effective renal denervation, it is important to provide a circumferential application of energy deployment. The first device was a single electrode, nonsteerable and later steerable, catheter (Symplicity/ARDIAN-Medtronic) receiving Communaute Europeenne-approval.…”
Section: Interventional Renal Denervationmentioning
confidence: 99%
“…In the last years, catheter-based renal denervation (RDN) has emerged as an interventional approach for safe BP reduction in patients with TRH [9][10][11][12][13][14][15][16]. Moreover, it was shown that RDN impacts on renal microcirculation, namely a reduction of albuminuria [17].…”
Section: Introductionmentioning
confidence: 99%